Charting the Emergence of National Identity in Children in Wales. (10th November 2017) - Murphy, Alison
Abstract : This multimodal study, set in Wales, demonstrates that children aged nine and ten can clearly define and rationalise their own national identity. It contributes to age related discussions on how children categorise themselves in terms of national identity and the rationale for their choices. The children in the study used single and multiple definitions of national identity and illustrate the increasing plural nature of 21st century Wales. Family, birthplace and residency were identified as factors in shaping their national identity, more so than language, despite the current bilingual policy drive in Wales.